Long-term survival, toxicities, and the role of chrono-chemotherapy with different infusion rates in locally advanced nasopharyngeal carcinoma patients treated with intensity-modulated radiation therapy: a retrospective study with a 5-year follow-up - Liu, Lina; Luo, Xunyan; Wu, Weili; Li, Yuanyuan; Long, Jinhua; Luo, Xiuling; Chen, Xiaoxiao; Gong, Xiuyun; Zhao, Chaofen; He, Qianyong; Li, Zhuoling; Shang, Kai; et al. (Frontiers in Oncology, 2024)
Purpose This study aimed to evaluate 5-year outcomes and the late toxicity profile of chrono-chemotherapy with different infusion rates in patients with locally advanced nasopharyngeal carcinoma (NPC). Methods and materials Our retrospective analysis included 70 patients with locally advanced NPC stages III and IVB (according to the 2010 American Joint Committee on Cancer staging system). Patients were treated with two cycles of induction chemotherapy (IC) before concurrent chemoradiotherapy (CCRT) at Guizhou Cancer Hospital. The IC with docetaxel, cisplatin (DDP) and fluorouracil regimen. Patients were divided into two groups during CCRT. Using a “MELODIE” multi-channel programmed pump, DDP (100 mg/m2) was administered for 12 hours from 10:00 am to 10:00 pm and repeated every 3 weeks for 2-3 cycles. DDP was administered at the peak period of 4:00 pm in the sinusoidal chrono-modulated infusion group (Arm A, n=35). The patients in Arm B received a constant rate of infusion. Both arms received radiotherapy through the same technique and dose fraction. The long-term survival and disease progression were observed. Results After a median follow-up of 82.8 months, the 5-year progression-free survival rate was 81.3% in Arm A and 79.6% in Arm B (P = 0.85). The 5-year overall survival rate was not significantly different between Arm A and Arm B (79.6% vs 85.3%, P = 0.79). The 5-year distant metastasis-free survival rate was 83.6% in Arm A and 84.6% in Arm B (P = 0.75). The 5-year local recurrence-free survival rate was 88.2% in Arm A and 85.3% in Arm B (P = 0.16). There were no late toxicities of grade 3-4 in either group. Both groups had grade 1-2 late toxicities. Dry mouth was the most common late toxic side effect, followed by hearing loss and difficulty in swallowing. There was no statistically significant difference between Arm A and Arm B in terms of side effects. Conclusion Long-term analysis confirmed that in CCRT, cisplatin administration with sinusoidal chrono-modulated infusion was not superior to the constant infusion rate in terms of long-term toxicity and prognosis.